REFORMING THE RAILWAY TRANSPORT IN COUNTRIES OF THE FORMER USSR - Barash, Yu. S. (Science and Transport Progress, 2010)
The article is devoted to analysis of reforming the railway transport in countries of the former USSR. Demerits and advantages of this process are determined.